Co-occurring Disordered Gambling Among Treatment-Seekers at a Community Outpatient Addiction Clinic. Issue 5 (September 2016) - Elman, Igor; Borodovsky, Jacob; Howard, Margaret; Scoglio, Arielle; Steinkamp, Jackson; Sobieszczyk, Amy; Mysels, David; Albanese, Mark
Abstract : Background: Parallel to the ongoing expansion of legalized gambling activities is a growing concern about rising occurrence of uncontrollable gambling. People with preexisting gambling and/or chemical addictions may be particularly vulnerable, but the extent of such co-occurring conditions and their demographic and clinical characteristics have not been sufficiently elucidated. To that end, the present study attempted to both, quantify the presence and to characterize co-occurring pathological or problem gambling (ie, respectively, at least 1- or at least 5 pathological gambling criteria from the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision ) among treatment-seeking patients at a community outpatient addiction program. Methods: The patients were assessed with the South Oaks Gambling Screen and their charts were reviewed for the extraction of demographic and clinical information according to a predetermined template. Data from 183 subjects withstood quality control procedures and were included. Results: The prevalence rates of co-occurring problem- (18.6%) and pathological (10.9%) gambling were strikingly higher than those found in the general population (2% and 0.5%, respectively). No increase in the clinical severity indices was observed across the gambling groups. Conclusions: Our data replicate those of prior studies reporting heightened prevalence of problematic gambling in patients with substance use disorders and extend the prior findings by including a subject population of treatment-seekers. In the era of the gambling industry growth, these results call for creation and/or adjustment of clinical addiction services to meet emerging preventive and therapeutic needs.